GAAP (generally accepted accounting principles) (Henry Stewart Talks, 2026)
Purpose of GAAP, Role of GAAP in communication, GAAP standard setting, Foundational GAAP principles, GAAP challenges with intangibles, GAAP and IFRS convergence